Neoliberalism Within Psychology Higher Education in Indonesia: A Critical Analysis - Teguh Wijaya Mulya (ANIMA Indonesian Psychological Journal, 2016)
Critical scholars have demonstrated the ways in which neoliberalism has increasingly become a dominant organising principle in current global political, economic, and social practices, including in higher education. This article aims to explore how and to what extent neo-liberal discourses have operated in a specific context, namely, in psychology higher education in Indonesia. To this end, the author examined policy documents published by relevant authorities such as AP2TPI, Dirjen DIKTI, and BAN-PT; and reflect on how those policies were enacted in the author’s 10-year experience as a psychology lecturer in a university in Indonesia. The results show that neoliberal discourses such as standardisation, competitiveness, and market orientation have underpinned the policies, curricula, and practices of psychology higher education in Indonesia. The author argues that such discourses (re)produce psychology students, graduates, and lecturers who are competitive, result-oriented, and market-driven. Consequently, democratic, humane, and organic ways of learning and practicing psychology have given way to more mechanistic, standardised, and box-ticking approaches to human behaviour.